Dynamic Response of a Bedding Rock Slope Reinforced by a Pile–Anchor Structure Under Earthquakes - Kaiyang Wang; Xianggui Yu; Zhuqiang Chu; Yanyan Li (Buildings)
Pile–anchor structures offer an effective way to reinforce slopes in earthquake-prone regions. Static and quasi-static analysis on pile–anchor structures has been widely conducted, but their dynamic behaviors have not been well addressed. This study explores the dynamic behavior of a bedding rock slope strengthened by pile–anchor structures in a seismic-prone region of China. We propose a method for the automatic application of viscoelastic boundaries and input of seismic waves in ABAQUS (version 2021) using MATLAB R2023a programming. A series of numerical simulations for the pile–anchor-reinforced slope under seismic motions with different acceleration amplitudes and excitation directions are performed. We find that the PGA amplification factors at the slope surface are larger than those in the middle of the slope, which is because the bedding planes near the slope surface cause reflections of seismic waves. The maximum axial force of the anchors of the upper and lower rows is greater than that of the middle rows. For example, under an acceleration amplitude of 0.1 g, the maximum axial forces of the anchors with numbers ranging from 1 to 6 are 466, 462, 461, 460, 461, and 463 kN, respectively. The distribution of the peak values of the earth pressure presents a significant change around the sliding surface. The maximum bending moment of the pile increases from 0.55 × 103 to 0.90 × 103 kN·m as the acceleration amplitudes of the seismic waves increase from 0.2 to 0.3 g, indicating that the pile can bear the load caused by the movement of the slope.